Homocysteine activates T cells by enhancing endoplasmic reticulum-mitochondria coupling and increasing mitochondrial respiration - Juan Feng; Silin Lü; Yanhong Ding; Ming Zheng; Xian Wang (Protein & Cell, 2016)
ABSTRACT Hyperhomocysteinemia (HHcy) accelerates atherosclerosis by increasing proliferation and stimulating cytokine secretion in T cells. However, whether homocysteine (Hcy)-mediated T cell activation is associated with metabolic reprogramming is unclear. Here, our in vivo and in vitro studies showed that Hcy-stimulated splenic T-cell activation in mice was accompanied by increased levels of mitochondrial reactive oxygen species (ROS) and calcium, mitochondrial mass and respiration. Inhibiting mitochondrial ROS production and calcium signals or blocking mitochondrial respiration largely blunted Hcy-induced T-cell interferon γ (IFN-γ) secretion and proliferation. Hcy also enhanced endoplasmic reticulum (ER) stress in T cells, and inhibition of ER stress with 4-phenylbutyric acid blocked Hcy-induced T-cell activation. Mechanistically, Hcy increased ER-mitochondria coupling, and uncoupling ER-mitochondria by the microtubule inhibitor nocodazole attenuated Hcy-stimulated mitochondrial reprogramming, IFN-γ secretion and proliferation in T cells, suggesting that juxtaposition of ER and mitochondria is required for Hcy-promoted mitochondrial function and T-cell activation. In conclusion, Hcy promotes T-cell activation by increasing ER-mitochondria coupling and regulating metabolic reprogramming.